BEHAVIOUR CHANGE THERAPY MODEL TRAINING IN EFFORTS TO CHANGE TOOTH BRUSHING BEHAVIOR PARENTS / GUARDIANS OF MENTAL RETARDED CHILDRENPELATIHAN MODEL BEHAVIOUR CHANGE THERAPY TERHADAP UPAYA PERUBAHAN PERILAKU MENGGOSOK GIGI ORANG TUA/ WALI ANAK RETARDASI - Laily, Rohisotul; Rasipin, Rasipin; Supriyana, Supriyana; Hadisaputro, Suharyo; Santoso, Bedjo (Journal of Applied Health Management and Technology, 2021)
ABSTRACTBackground: Dental and oral health problems of most people, including mental retardation children. Child health policy mental retardation with all its limitations requires the participation of parents/ guardians. Brushing teeth behavior of parents in increasing motivation to brush children's teeth mentally retarded. Strategies for providing dental health education in accordance with the needs and abilities of children are needed. Behavior change therapy model in parents/ guardians is a learning model as a skill in brushing children's teeth mentally retarded. Puspose: The purpose of this study is to produce a behavior change therapy model that is able to improve the brushing behavior of parents/ guardians of children with mental retardation. Methods: Research and Development (R & D) procedures there are 5 stages of gathering information, design models, expert validation and revision, test models, the final results of the model. The sample collected 32 parents / guardians. Sampling using a purposive sampling technique. Data on the model results were tested by paired different tests, intergroup difference tests, and proportion. Results: The results of this study, obtained about changes in significant in increasing knowledge knowledge (0.000), attitudes (0.000), skills (0.000) parents/ guardians. Conclusion The model of appropriate and effective behavior change therapy is effective in increasing the brushing of teeth of parents / guardians of children with mental retardation.Â Keywords: Behaviour change therapy models, tooth brushing behavior, parents/ guardians of children with mental retardation.Â